Mongolia Financial Sector Assessment : Access to Finance - World Bank (Washington, DC, 2017)
Mongolia's economy has embarked on a very high, long-term growth trajectory. To realize fully its economic potential, Mongolia needs to build a diversified, efficient and stable financial system, capable of intermediating both on a large scale and in specific market segments. Access to financial services in Mongolia is relatively high when measured by the demographic penetration of branches. The aim of this technical note is to assess the level of access to finance in Mongolia, and especially for Micro, Small and Medium Enterprises (MSMEs), to identify key obstacles to improving access, and to provide recommendations to overcome these obstacles. The technical note is organized as follows. Section one provides a broad overview of the macroeconomic environment and is followed by section two on the status of access to finance in Mongolia. Section three discusses products and market segments. Section four examines the supply of financial services by analyzing the role of key market players. Section five examines the demand for financial services by drawing on enterprise surveys to assess firms perceptions of their access to finance, and analyzes financing conditions for MSMEs. Section six examines obstacles in the regulatory, supervisory framework, and financial infrastructure for access to finance. Section seven describes the main government programs related to access to finance. In conclusion, section eight provides policy recommendations for overcoming obstacles to enhancing access to finance.